STANDARDIZATION OF NELUMBO NUCIFERA PLUMULE AND DETERMINATION OF NEFERINE CONTENT BY TLC-DENSITOMETRY AND TLC-IMAGE ANALYSIS - Uacharoen, Kanokwan; Palanuvej, Chanida; Ruangrungsi, Nijsiri (Interprofessional Journal of Health Sciences, 2023)
Plumule of Nelumbo nucifera Gaertn., a traditional Thai medicine, is primarily used for nervous disorder and high fevers. Neferine is the main alkaloid component in N. nucifera plumule and has been reported to possess several pharmacological properties. Standardization of plant materials is necessary for an assurance of quality, efficacy and safety based on various parameters. This study aimed to investigate the pharmacognostic specification of N. nucifera plumule and determine the neferine content using TLC-densitometry and TLC-image analysis. Transverse section of this crude drug showed the anatomical characteristics of epidermis, air chamber, parenchyma and vascular bundle. Additionally, the histological study of powder showed anomocytic stomata, parenchyma with starch granule and layer of cotyledons. TLC fingerprint and physicochemical constants were also established. The results of total ash, acid insoluble ash, loss on drying, moisture content, ethanol and water extractive values were found to be 3.86 ± 0.17, 0.54 ± 0.04, 9.91 ± 0.09, 10.02 ± 0.72, 16.54 ± 1.34 and 28.27 ± 2.01 g%, respectively. Moreover, TLC-densitometry and TLC-image analysis methods were validated for determination of neferine content in N. nucifera plumule. The calibration range was between 0.25-3.0 μg/spot and exhibited suitable accuracy, precision and robustness in both methods. Neferine content in N. nucifera plumule were 0.495 ± 0.186 g% by TLC-densitometry and 0.497 ± 0.189 g% by TLC-image analysis. Information obtained from this study can be used for the identification and standardization of N. nucifera plumule and also toward monograph development on this plant.